Prevention and control of diabetes mellitus complications in productive population in rural - Nurlatif, Rr. Vita; Sumardiyono, Sumardiyono; Rahardjo, Setyo Sri (Intelektual Pustaka Media Utama, 2024)
In Pekalongan Regency, Central Java, Indonesia, cases of productive population with diabetes mellitus have rapidly increased over the past three years. With regard to individual-based problems prevention and management, this is not sufficiently balanced. From the standpoint of the provider, this study examines attempts to prevent and control diabetes mellitus in productive population, including obstacles and limitations. With a focus on three rural areas (Wiradesa, Tirto I and Kedungwuni I Sub-Districts), qualitative study included 75 productive-age diabetics and 30 breadwinners. In-depth interviews and focus group discussions were used to gather data, which was then thematically analyzed. Three rural locus with the highest prevalence of diabetes mellitus in productive population were found in the results. Through screening for non-communicable diseases at integrated service post (Posyandu), chronic disease management programs and cross-sectoral activities, there are numerous initiatives for the prevention and management of complications. The challenges include constantly changing programmers, programmers with many assignments, inadequate target awareness and low motivation, as well as a worse recording and reporting system. Such that fundamental information on both individual and public health cannot be accessed. Based on individual emphasis, recording and reporting, several programs for complication prevention and management are required to identify the range of non-communicable diseases.